Salah Boubnider and his role in the national movement and the Algerian revolution (1945-1962) - Laabidi, Idriss (The Algerian Historical Journal, 2026)
The Algerian revolution in general, and the second region in particular (North Constantine), gave birth to a leader who belongs to the military category first, who was able to reach the highest ranks of leadership in the revolution gradually from an official for the “Wadi El-Zanati” region in the outskirts of “Guelma” and then a leader of the attacks of August 20, 1955 in “Al-Kharoub” And he is rewarded with responsibility for the “Ain Karma” area on the outskirts of “Constantine”, and when “Ali Kafi” assumed the leadership of the second state, he appointed him as a military official in 1957, which allowed him to be a member of the Council of the second state and from him a member of the National Council of the Algerian Revolution, and ended with The matter was up to the leader of the same province in the spring of 1959 until 1962... He is "Saleh Bubnaidar", known as "Sawt al-Arab" or "Si Saleh" as his comrades in arms call him